video promosi pemandian air panas Banyuwedang di Desa Pejarakan - Ahmad Sidik; Nicholaus Wayong Kabelen (Jurnal Desain Komunikasi Visual Asia, 2021)
Buleleng is a Regency in Bali, one of which is rich in natural scenery, it can even be said that Buleleng is the most complete area and has unique objects and attractions that attract interest. tourists to visit it. One of the Tourism Objects in Buleleng Regency is located in Gerokgak District, Pejarakan Village, namely Banyuwedang Hot Springs Tourism Object. Hot Water which is the main icon of this location comes from hot springs that appear on the beach. So far, Banyuwedang hot springs only do promotions through guides from nearby hotels or during Hindu holidays to visit this tourist spot, plus there are no promotional videos, posters, merchandise and browsers to promote. From the above problems, it is necessary to make promotions that can introduce Banyuwedang Hot Springs tourism. By making promotional videos, one of which can make hot springs more widely known, not only by local people but also by outsiders.